Fusão de imagens de tomografia por impedância elétrica - Viganó, Guilherme (My University, 2019)
Electrical impedance tomography (EIT) is a promising, non-invasive and radiation-free technique capable of producing images of the internal impedance distribution of a body in real time. Although it allows the construction of images with high temporal resolution, EIT presents a very limited spatial resolution, when compared with other technologies such as computed tomography (CT) and magnetic resonance imaging (MRI). The present work proposes the search for improvements in the spatial resolution through post-processing the tomographic images. A single similar approach found in the literature proposes the Super-Resolution of the tomographic images, technique known for its high computational cost. In this work, it is proposed the additive fusion of EIT images, which presents computational cost more compatible with real time applications. The results obtained indicate that, due to the nature of the problem of this type of tomography, the additive fusion is able to achieve the Super-Resolution, considerably improving the quality of the tomographic images at a low computational cost when compared to the already consolidated post-processing techniques in the area.(sic)
A tomografia por impedância elétrica (TIE) é uma técnica promissora, não invasiva, capaz de produzir imagens da distribuição de impedâncias internas de um corpo em tempo real. Apesar de permitir a construção de imagens com alta resolução temporal, a TIE apresenta resolução espacial muito limitada, quando comparada às outras técnicas de obtenção de imagens como tomografia computadorizada (TC) e ressonância magnética nuclear (RMN). O presente trabalho propõe a busca de melhorias na resolução espacial através de um pós-processamento das imagens tomográficas. Uma única abordagem similar encontrada na literatura propõe a Super-Resolução das imagens tomográficas, técnica esta conhecida por seu elevado custo computacional. Neste trabalho, é proposta a fusão aditiva das imagens de TIE, que apresenta um custo computacional mais compatível com aplicações em tempo real. Os resultados obtidos indicam que, pela natureza do problema desse tipo de tomografia, a fusão aditiva é capaz de alcançar a Super-Resolução, melhorando consideravelmente a qualidade das imagens tomográficas a um baixo custo computacional, quando comparado às técnicas de pós-processamento já consolidadas na área.(sic)
Keywords: Tomografia; Processamento de imagens